Skull Bone Flap Fixation – Reliability and Efficacy of a New Grip-Like Titanium Device (Skull Grip) versus Traditional Sutures: A Clinical Randomized Trial - Chibbaro, S.; Makiese, O.; Bresson, D.; Hamdi, S.; Cornelius, J. F.; Guichard, J. P.; Reiss, A.; Bouazza, S.; Vicaut, E.; Ricci, A.; Galzio, R.; Poczos, P.; George, B.; Marsella, M.; Di Emidio, P. (min - Minimally Invasive Neurosurgery, 2011)
After completing a craniotomy, it is important to replace the removed bone flap in its natural position in order to guarantee brain protection as well as improve cosmesis. A skull defect can expose the brain to accidental damage, and in cases of larger defects it may also cause the patients psychosocial problems. The ideal fixation device should provide reliable attachment of the flap to the skull and promote fast bony healing to avoid possible pseudo-arthrosis and/or osteolytic changes.This is a pilot randomized clinical trial on a series of 16 patients undergoing different craniotomies for benign brain lesions in which the bone flaps were replaced using traditional sutures (Prolene 0.0) in 8 cases and with a new skull fixation device (Skull Grip) in the other 8 (randomly allocated). All patients underwent CT scans of the head with 3D reconstruction at day 1 and day 90 postoperatively to evaluate bone flap position and fusion. These scans were independently reviewed by a neuroradiologist. Cosmesis was also evaluated clinically by the surgeon and radiologically by the neuroradiologist in the 2 patient groups.The new “Skull Grip” device has shown stronger fixation qualities with optimal bone flap fusion and increased cosmetic healing features vs. traditional sutures.The “Skull Grip” has shown to be a reliable, effective and stronger bone flap fixation device when compared to traditional sutures.
Keywords: cranial bone flap; skull flap fixation; titanium implants